A Novel One-Pot Synthesis of N,N-Dimethylaminopyridines by Diazotization of Aminopyridines in Dimethylformamide in the Presence of Trifluoromethanesulfonic Acid; Russian Journal of Organic Chemistry; Vol. 56, iss. 6 - Sanzhiev A. N. Aldar Nikolaevich; Potapova M. I. Marina Igorevna; Krasnokutskaya E. A . Elena Aleksandrovna; Filimonov V. D. Viktor Dmitrievich (2020, 2020)
Title screen